Adsorption mechanism of reactive dyes onto modified coal-fired bottom ash: equilibrium and thermodynamics study / Hawaiah Imam Maarof, Norhaslinda Nasuha and Nor Aida Zubir - Imam Maarof, Hawaiah; Nasuha, Norhaslinda; Zubir, Nor Aida (Research Management Institute (RMI), 2012)
Adsorption has been recognized to be a promising process to remove colours from aqueous solution (Xue, et al., 2009). Utilizing of agricultural and industrial wastes as adsorbents had been explored by many researchers. However, the study of coal-fired bottom ash as adsorbent for dye adsorption is scanty reported by researcher. In fact, the influence of complex properties of coal-fired bottom ash to the adsorption system have not yet been explored in detailed. Therefore, the study on the adsorption mechanism of dye onto coal-fired bottom ash as well as modified coal-fired bottom ash is needed in improving its capability of dyes adsorption process. The physical and chemical properties of an adsorbent serve significant effects to the adsorption process. Chemical properties include the degree of ionization of the adsorbent surface, the types of functional group which are present on the adsorbent and degree to which these properties may changed by contact with the solution (Bernardin, 1985). Some adsorbents have affinity for H+ and OH' ions, which will directly affect the solution pH, solubility and adsorption capacity. The mechanism might vary from reversible to strong chemical interaction with the presence of active functional groups on the adsorbent surface (Bernardin, 1985). In this study, the equilibrium and thermodynamics studies will be carried out on specific pair of reactive dye-bottom ash and modified coal-fired bottom ash system.